(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Biogas is going through a time of tremendous growth, and biogas upgrading is getting a lot of attention. As a consequence, the biogas upgrading business has significant challenges in terms of energy consumption and operating costs. The technique of upgrading is determined on a site-by-site, case-by-case basis, and depending on biogas consumption requirements and local variables. Like a reason, it’s crucial to match the technology used to specific requirements. The current state of biogas cleaning and upgrading technologies is investigated, comprising product purity and pollutants, methane recovery as well as loss, upgrading efficiency, and capital and operational costs. Furthermore, the potential usage of biogas, as well as the consequent gas quality requirements, are fully investigated. The outcomes of comparisons between both the technical features of upgrading technologies, the specific demands for different gas usage, as well as the corresponding investment and operating costs are used to provide suggestions for appropriate technology.